2017
DOI: 10.1093/nar/gkx007
|View full text |Cite
|
Sign up to set email alerts
|

From benchmarking HITS-CLIP peak detection programs to a new method for identification of miRNA-binding sites from Ago2-CLIP data

Abstract: Experimental evidence indicates that about 60% of miRNA-binding activity does not follow the canonical rule about the seed matching between miRNA and target mRNAs, but rather a non-canonical miRNA targeting activity outside the seed or with a seed-like motifs. Here, we propose a new unbiased method to identify canonical and non-canonical miRNA-binding sites from peaks identified by Ago2 Cross-Linked ImmunoPrecipitation associated to high-throughput sequencing (CLIP-seq). Since the quality of peaks is of pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
(108 reference statements)
2
34
0
Order By: Relevance
“…Similarly, we found that the direct reduction of the binding sites for the endogenously expressed miRNAs (endogenous Ago2-miRNA peaks; Supplementary Fig. 6e ) 34 in P19 cells upon Sfpq knockdown statistically only occurred in the 3′UTR (Fig. 4e and Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Similarly, we found that the direct reduction of the binding sites for the endogenously expressed miRNAs (endogenous Ago2-miRNA peaks; Supplementary Fig. 6e ) 34 in P19 cells upon Sfpq knockdown statistically only occurred in the 3′UTR (Fig. 4e and Supplementary Fig.…”
Section: Resultssupporting
confidence: 54%
“…To assess the Sfpq dependency of the endogenous miRNA-binding sites, we selected Ago2 peaks that overlap (Jaccard index > 0.10) between the full set of 2065 Ago2-miRNA peaks identified by HITS-CLIP analysis from P19 cells 34 and the Ago2-miRNA peaks enriched in siCtr-transfected P19 cells over the siSfpq-transfected P19 cells condition identified by dCLIP analysis. We found that 245 Ago2-miRNA peaks overlap with the peaks coming from such a filter, indicating their dependency on Sfpq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further complicated by the different strategies in identifying the crosslink sites by the various experimental protocols ( Table 1, Supplementary Table 1). Benchmarking of tools is challenging, owing to the differences in experimental protocols, and our limited understanding of the ground-truth regarding RNA binding sites in vivo (33,34) . Nevertheless, we attempt to demonstrate the impact of the different CLIP protocols and computational tools through use of the RNA maps, which combine CLIP with orthogonal functional data to derive an estimate of ground-truth from the perspective that RNA landmarks regulated by an RBP should contain its nearby RNA binding sites (Box 1).…”
Section: Peak Callingmentioning
confidence: 99%
“…Mapping of RBP and miRNA transcript specificity using high-throughput approaches like crosslinking and immunoprecipitation (CLIP) technologies [45, 46] will allow us to resolve the cell type and stimulus-specific RBP-miRNA interactions that shape host immunity.…”
Section: Mirna Function In the Context Of Other Post-transcriptional mentioning
confidence: 99%